STUDY OF RESISTIVITY SOUNDING METHOD IN MONITORING OF ACID MINE DRAINAGE FORMING ON COAL MINE OVERBURDEN - ARIEF PRASETYONO (NIM : 22114013), DIAS
Minerals in exposed rock cover material have the potential to form acid mine drainage (AMD) in case of contact with air and water. Resistivity sounding method is used in the delineation of saturated and unsaturated layers, further from those two zones the determination of the area with the potential for AMD formation and the sulfate accumulation area. Data has collected in the area of coal mine overburden. The first location (pit H) is carried out by two measuring points, while four measuring points are performed at the second location (pit J). The sounding point is around the well monitor the embankment area. DZA monitor wells are in the pit H area, while pit J has four monitored wells (DMN, DMU, DMD, and DMS). Monitored water well samples were taken as many as 2500 mL for water quality testing related to ionic composition in water. Based on the well water quality monitored can be known hydrochemical facies from well water monitor. The use of the resistivity sounding method can define the saturated and unsaturated zones based on the contrast of the resistivity values between layers, in the first location providing saturation zone information up to 19.3 m depth from the surface and at a depth of 36.7 - 69 m with a resistivity range of 4.9 - 19.4 ohm.m, while the second location, the saturation zone is at depth of 1.9 - 8.2 m with a resistivity range of 0.6 - 7.2 ohm.m. Estimation of potential area of AMD formation on pit of H and pit J through correlation of sounding column data with concentration of well water sulfate monitor. From the correlation result, the area with AMD formation potential is in the range of resistivity value 1.6 - 6.7 ohm.m and is in the unsaturated zone, and under water level condition is suspected to be the accumulation area of sulfate. The accuracy of the subsurface model can be improved by using a combination of sounding and profiling.